When Should Genetic Testing Be Performed in Epilepsy Patients? - Poduri, Annapurna (Epilepsy Curr, 2017)
This review is a summary of a talk presented at the 2015 American Epilepsy Society Annual Meeting. Its purposes are 1) to review developments in epilepsy genetics, 2) to discuss which groups of patients with epilepsy might benefit from genetic testing, and 3) to present a rational approach to genetic testing in epilepsy in the rapidly evolving era of genomic medicine.